STUDY OF OPERATIONAL DYNAMIC LOADS IN THE LIFTING MECHANISM OF THE PORTAL CRANE “GANZ” DURING THE TRANSSHIPMENT OF BULK CARGO - STRELBITSKYI, VIKTOR (Herald of Khmelnytskyi National University. Technical sciences, 2024)
Portal grab cranes are an integral part of port infrastructure used to handle bulk materials, including grain, ore, coal, and other dry bulk cargo. However, due to the difficult economic situation, more than 90% of port cranes have reached the end of their standard service life. The supply of new machines to ports remains limited. Since portal cranes play a key role in technological processes, their reliability and uninterrupted operation are critical to the efficiency of port terminals.Numerous studies have confirmed that fatigue failure, which occurs due to excessive cyclic loads, is the main cause of crane accidents . The intense load cycles inherent in crane operations accelerate the manifestation of this fatigue process. However, the dynamic loads on gantry cranes that have been in operation for more than 40 years remain insufficiently studied. Each individual crane requires a special analysis, since the dynamic characteristics of the mechanisms depend on the conditions of their operation, as well as on the geometric, physical, and mechanical properties of its components.Given that the forces in the ropes of lifting systems depend on many factors that are difficult or even impossible to take into account during modeling, they are most often determined using experimental methods. The paper presents experimental studies of dynamic forces in the lifting mechanism of grab portal cranes “Ganz” with extended service life during sand handling. The object of research is used for handling bulk materials in a seaport. The electrotensometric method was used to determine the dynamic forces. In the course of the research, the lifting speed was simultaneously measured using tachometers that were mounted coaxially with the motor shafts.Based on the experimental data obtained, the probabilistic characteristics of the distribution of operational values of dynamic loads in the lifting mechanism were determined.  The analysis of the data obtained showed that when overloading loads weighing from 8 to 16 tons, the values of the dynamism coefficients in the closing ropes vary from 1.2 to 2. The calculated dynamism coefficients exceed those recommended for gantry cranes, which indicates an overload of the lifting mechanisms. The histogram of the probability distribution of the weight of the load lifted by the crane per work cycle showed that during operation, the crane mainly overloads from 13 to 15 tons of the load being lifted, taking into account the weight of the grab.
Keywords: portal crane; dynamic forces; lifting mechanism; dynamic coefficient